2022
DOI: 10.1002/2211-5463.13524
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes contributing to cisplatin resistance in osteosarcoma cells

Abstract: Osteosarcomas are prevalent in children and young adults and have a high recurrence rate. Cisplatin, doxorubicin, and methotrexate are common adjuvant chemotherapy drugs for treatment of osteosarcoma, but multidrug resistance is a growing problem. Therefore, understanding the molecular mechanisms of chemotherapy resistance in osteosarcoma cells is crucial for developing new therapeutic approaches and ultimately improving the prognosis of osteosarcoma patients. To identify genes associated with cisplatin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…In the research of Xiang et al, the colorectal cancer patients with higher expression of CGREF1 were found to have significantly better overall survival than patients with lower expression, and the role of CGREF1 in the prognosis of Early-onset colorectal cancer was reported [33]. Furthermore, Xie et al observed that CGREF1 expression were high in the tissue of osteosarcoma patients while it were lowly expressed in normal tissue, and speculated that CGREF1 can predict drug resistance to osteosarcoma [34]. However, the biological function of CGREF1 is poorly explored, and further study for its mechanisms and roles in these diseases is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In the research of Xiang et al, the colorectal cancer patients with higher expression of CGREF1 were found to have significantly better overall survival than patients with lower expression, and the role of CGREF1 in the prognosis of Early-onset colorectal cancer was reported [33]. Furthermore, Xie et al observed that CGREF1 expression were high in the tissue of osteosarcoma patients while it were lowly expressed in normal tissue, and speculated that CGREF1 can predict drug resistance to osteosarcoma [34]. However, the biological function of CGREF1 is poorly explored, and further study for its mechanisms and roles in these diseases is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…REEP3 is known to play a role in adipocyte generation and differentiation 15 . Recent studies have shown that REEP3 is significantly expressed in different types of tumors, with implications for tumor invasiveness and prognosis 16 , 17 . This suggests that REEP3 could potentially enhance the migratory and invasive abilities of tumor cells by influencing cell adhesion and cytoskeletal rearrangement.…”
Section: Introductionmentioning
confidence: 99%